Literary studies in the age of the empire's collapse - San Juan, Epifanio, Jr. (Iloilo City UP in the Visayas, 2009)
"Literary studies in the global North after WWII served chiefly the interests of pax Americana. After 9/11 and the end of the Cold War, it functioned as the ideological weapon to maintain U.S. hegemony and geopolitical control of energy resources. But when US scholars realized that postmodern theories (Derrida, Foucault, etc.) will not preserve the bankruptcy of Eurocentric ideology, they reverted to neopragmatism and cynical relativism. A revival of nominalist and philosophical idealist theories, such as aestheticism, tried to save reactionary artists (like William Faulkner) from obsolescence. However, the global collapse of finance captialism is undermining this return to metaphysicss, hence the need to engage in critique to expose the moribund system and initiate the beginnings of global socialist transformation."
Keywords: Literature; Literary studies